Podatki a atrakcyjność inwestycyjna Polski na tle krajów Unii Europejskiej - Stawicka, Magdalena (Taxes and investment attractiveness in the countries of the European Union and in particular Poland, 2006)
The fundamental element of macroeconomic policy which is very important for foreign investors is the level of taxes. The reducing of taxes influences the greater possibility of inflow of direct foreign investments and encourages the investors to payment in data of country the taxes. The aim of the article is to analyze the tax systems - countries of the European Union as a point of reference of attractiveness of individual states for foreign investors. The aim of the analysis and consideration is to find the answer to the question whether low taxes are very important element in the fight of EU countries for direct foreign investments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 132-142